Staphylococcus aureus Toxins: An Update on Their Pathogenic Properties and Potential Treatments - Nour Ahmad-Mansour; Paul Loubet; Cassandra Pouget; Catherine Dunyach-Remy; Albert Sotto; Jean-Philippe Lavigne; Virginie Molle (Toxins, 2021)
Staphylococcus aureus is a clinically important pathogen that causes a wide range of human infections, from minor skin infections to severe tissue infection and sepsis. S. aureus has a high level of antibiotic resistance and is a common cause of infections in hospitals and the community. The rising prevalence of community-acquired methicillin-resistant S. aureus (CA-MRSA), combined with the important severity of S. aureus infections in general, has resulted in the frequent use of anti-staphylococcal antibiotics, leading to increasing resistance rates. Antibiotic-resistant S. aureus continues to be a major health concern, necessitating the development of novel therapeutic strategies. S. aureus uses a wide range of virulence factors, such as toxins, to develop an infection in the host. Recently, anti-virulence treatments that directly or indirectly neutralize S. aureus toxins have showed promise. In this review, we provide an update on toxin pathogenic characteristics, as well as anti-toxin therapeutical strategies.